2009
DOI: 10.1080/13550280802338652
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of virological and immunological parameters in subjects from South India infected with human immunodeficiency virus type 1 clade C and correlation of findings with occurrence of neurological disease

Abstract: Several studies carried out in Western countries have demonstrated that a number of virological and immunological markers such as viral loads, cytokines, beta(2)-microglobulin, neopterin, etc., are elevated in the serum and cerebrospinal fluid (CSF) of human immunodeficiency virus (HIV)-infected individuals with neurological disease. The neurological manifestations of HIV infection noted in Indian patients is different from those reported in Western countries. Moreover, few studies have investigated the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In addition, levels decrease with antiretroviral treatment. 29 This finding has been replicated in HIV-1 clade C. 19 Elevated CSF neopterin correlates with HIV dementia severity. 29 In patients with advanced HIV disease, elevated levels are associated with increased risk of dementia.…”
Section: 28mentioning
confidence: 54%
See 1 more Smart Citation
“…In addition, levels decrease with antiretroviral treatment. 29 This finding has been replicated in HIV-1 clade C. 19 Elevated CSF neopterin correlates with HIV dementia severity. 29 In patients with advanced HIV disease, elevated levels are associated with increased risk of dementia.…”
Section: 28mentioning
confidence: 54%
“…18 The generalizability of β2M elevation in neurological involvement of HIV-1 Clade C has recently been described. 19 However, it is usually not useful in CART-treated patients.…”
Section: 16mentioning
confidence: 99%
“…However, it was shown that in India, occurrence of neurocognitive deficits among HAART naïve, HIV-1 clade C-infected individuals was similar to that occurring in the West with HIV-1 clade B infection (Gupta et al 2007). It was also reported that inflammatory cytokines and virological markers were significantly increased in cerebral spinal fluid (CSF) of infected individuals (Kamat et al 2009). A critical gap for research in India is the lack of normative data from HIV negative comparison groups.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma viral load estimation is the best indicator of how active HIV is in the patient's body, whereas the absolute CD4 cell count is more predictive of clinical disease progression. In the beginning of HIV epidemic, various other markers such as b2 microglobulin, neopterin and various cytokines have been considered as the surrogate markers to monitor the disease progression [59][60][61][62][63]. Although nonspecific, these makers gave fairly good idea about the immune activation and thus the disease progression in HIV infected individuals.…”
Section: Monitoring Of Hiv Disease Progressionmentioning
confidence: 99%